2021
DOI: 10.3390/nu13030879
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Consumption of Beer and Its Effects on Cardiovascular and Metabolic Health: An Updated Review of Recent Scientific Evidence

Abstract: There is growing interest in the potential health-related effects of moderate alcohol consumption and, specifically, of beer. This review provides an assessment of beer-associated effects on cardiovascular and metabolic risk factors to identify a consumption level that can be considered “moderate”. We identified all prospective clinical studies and systematic reviews that evaluated the health effects of beer published between January 2007 and April 2020. Five of six selected studies found a protective effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 75 publications
0
35
0
Order By: Relevance
“…The observed contrasting results reported in this meta-analysis may depend on the different age ranges included in the original studies, since the risk of osteoporosis and detrimental effects of alcohol on bone health spike after menopause [51]. Moreover, some studies have reported that women may have a higher sensitivity to alcohol and, therefore, their upper limit for moderate consumption might be slightly lower than for men [55]. Finally, alcohol may indirectly play a role in individuals' BMI, as well as their lean and fat mass-which, in turn, has been shown to differentially contribute to BMD in men and women (stronger relationship in men than in premenopausal women) [56].…”
Section: Discussionmentioning
confidence: 81%
“…The observed contrasting results reported in this meta-analysis may depend on the different age ranges included in the original studies, since the risk of osteoporosis and detrimental effects of alcohol on bone health spike after menopause [51]. Moreover, some studies have reported that women may have a higher sensitivity to alcohol and, therefore, their upper limit for moderate consumption might be slightly lower than for men [55]. Finally, alcohol may indirectly play a role in individuals' BMI, as well as their lean and fat mass-which, in turn, has been shown to differentially contribute to BMD in men and women (stronger relationship in men than in premenopausal women) [56].…”
Section: Discussionmentioning
confidence: 81%
“…Wine consumption has been widely studied due to its beneficial effects on cardiovascular and metabolic health [ 10 ]. However, most studies have evaluated wine intake using FFQs or self-questionnaires instead of biological biomarkers, a more reliable and objective way of assessing dietary habits [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modifiable factors, such as smoking cessation, healthy diet, and regular physical activity, play a crucial role in reducing cardiovascular risk [ 9 ]. The Mediterranean diet (MedDiet) has been associated with a better control of several CVRFs [ 10 ] through improvements in BP, lipid profile, glucose metabolism, arrhythmia risk, and gut microbiome [ 11 , 12 ]. One of the main characteristics of the MedDiet is the abundant consumption of olive oil, vegetables, fruits, nuts, legumes, fish, and cereals, and moderate wine consumption [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol use disorders (AUD) continue to be a major problem in western countries like the UK partly because of its increased affordability, where alcohol is 74% more affordable in 2019 than it was in 1987 [1] . Although there are several reports that suggest the positive effects of moderate alcohol intake on cardiovascular health [2] the general effect of problematic alcohol use on society is overwhelmingly negative with 24% of adults in the UK drinking over the recommended 14 units a week, a level of alcohol intake that increases the risks of developing cancers, cardiovascular diseases and liver disease [3] . Worldwide, alcohol causes 5.3% of all deaths (>3 million people per year) and accounts for 132.6 million disability adjusted life years [3] .…”
Section: The Problem At Handmentioning
confidence: 99%